Cyber Security for Multi-Station Integrated Smart Energy Stations: Architecture and Solutions - Yangrong Chen; June Li; Qiuyu Lu; Hai Lin; Yu Xia; Fuyang Li (Energies, 2021)
Multi-station integration is motivated by the requirements of distributed energies interconnection and improvements in the efficiency of energy systems. Due to the diversity of communication services and the complexity of data exchanges between in-of-station and out-of-station, multi-station integrated systems have high security requirements. However, issues related to cyber security for multi-station integrated systems are seldom explored. Hence, this paper designs the secondary system architecture and proposes cyber security protection solutions for smart energy stations (SESt) that integrate the substation, photovoltaic station, energy storage station, electric vehicle charging station, and data center station. Firstly, the composition of SESt and functions of each substation are presented, a layered architecture of SESt is designed, and data exchanges of SESt are analyzed. Then, the cyber security threats and requirements of SESt are illustrated. Moreover, the cyber security protection principle and a cyber security protection system for SESt are proposed. On this basis, a security zoning and isolation scheme for SESt is designed. Finally, a traffic isolation scheme based on virtual local area networks (VLANs), a real-time guarantee scheme for communications based on service priority, and an enhancing cyber security scheme based on improved IEC 62351 are proposed for SESt.